2022
DOI: 10.1038/s41467-022-28273-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep phenotyping of Alzheimer’s disease leveraging electronic medical records identifies sex-specific clinical associations

Abstract: Alzheimer’s Disease (AD) is a neurodegenerative disorder that is still not fully understood. Sex modifies AD vulnerability, but the reasons for this are largely unknown. We utilize two independent electronic medical record (EMR) systems across 44,288 patients to perform deep clinical phenotyping and network analysis to gain insight into clinical characteristics and sex-specific clinical associations in AD. Embeddings and network representation of patient diagnoses demonstrate greater comorbidity interactions i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 123 publications
4
23
0
Order By: Relevance
“…First, we asked whether patients' phenotypic profiles differed by AD status, identified R&E, and UC location using low-dimensional embedding (UMAP). For AD status, significant differences were found between patients with AD and controls along both UMAP components at UCSF and in the validation cohort, consistent with Tang et al 7 This suggests that representing patients using ICD diagnoses mapped to phenotypes yield similar results to using ICD diagnoses directly, providing support for the use of phenotypes to investigate patient comorbidities. Next, while we found numerous differences between patients' phenotypic profiles based on identified R&E at UCSF, many of these differences were not corroborated in the validation cohort, with the exception that Black-identified patients' phenotypic profiles were found to be significantly different from Latine-and White-identified patients' phenotypic profiles along the first UMAP component.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…First, we asked whether patients' phenotypic profiles differed by AD status, identified R&E, and UC location using low-dimensional embedding (UMAP). For AD status, significant differences were found between patients with AD and controls along both UMAP components at UCSF and in the validation cohort, consistent with Tang et al 7 This suggests that representing patients using ICD diagnoses mapped to phenotypes yield similar results to using ICD diagnoses directly, providing support for the use of phenotypes to investigate patient comorbidities. Next, while we found numerous differences between patients' phenotypic profiles based on identified R&E at UCSF, many of these differences were not corroborated in the validation cohort, with the exception that Black-identified patients' phenotypic profiles were found to be significantly different from Latine-and White-identified patients' phenotypic profiles along the first UMAP component.…”
Section: Discussionsupporting
confidence: 83%
“…This suggests that AD networks are relatively more connected, with many shared phenotypes amongst patients. Degree and neighborhood connectivity were also found to be higher for patients with AD relative to controls in Tang et al 7 For AD networks representing Asian-identified patients specifically, closeness centrality was higher, while average shortest path length and eccentricity were lower relative to matched control networks at UCSF and in the validation cohort; closeness centrality was also found to be higher for AD relative to controls in Tang et al This suggests that phenotypes in Asian-identified patients with AD are more closely connected to one another relative to controls. Finally, for AD networks representing Latine-identified patients at UCSF and in the UC-wide validation cohort, stress was found to be higher relative to matched control networks; stress was also found to be significantly different in Tang et al This suggests that phenotypes are relatively more connected to one another for Latine-identified patients with AD.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…While men diagnosed with AD seem to progress to death quicker, women with increased tau pathology can exhibit greater cognitive resilience [ 202 , 203 ]. The underlying causes for sex differences in prevalence and vulnerability to AD are currently subject to a lively debate in the field [ 204 ], with an increasing amount of studies trying to delineate sex-specific clinical associations [ 205 ]. Among women, changes in hormonal exposure—such as early sudden, surgical menopause—are associated with more rapid cognitive decline and a greater burden of neuritic amyloid plaque on autopsy [ 206 ].…”
Section: Sexual Dimorphism In Neuroinflammation and Ad Developmentmentioning
confidence: 99%